Technology used to increase the quality of fermented beverages from aronia and honey - Vanghele, Nicoleta Alexandra; Begea, Mihaela; Pruteanu, Augustina Mirabela; Begea, Mihaela (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
In recent years, there has been a global increase in the population concerns about the quality of the food they consume. A new tendency is to include new products that present various health advantages in everyday diets. Honey is an important component for the human diet, due to its use as a sweetener and in the production of sweet foods. Due to its medicinal properties, particularly in the treatment of pulmonary and digestive disorders, it is believed to be one of the products most frequently referenced in ancient traditional medicine documents. Aronia fruits are a rich source of antioxidants, bringing many health benefits. Fermentation is a biochemical reaction that occurs anaerobically and transforms an organic substrate under the action of microbial enzymes. These enzymes are produced by microorganisms such as yeasts, bacteria and fungi. Getting a fermented beverage out of aronia and honey is a way to conserve these products because by using fermentation the nutritional or organoleptic qualities of certain products are transformed and improved.